Nonlinear Analysis of High Strength Concrete Frames under Cyclic Loading - Mahmood, Abdulkareem Darweesh (Sulaimani Journal for Pure and Applied Sciences, 2007)
A computer program has been developed to prediet the behavior of high strength reinforced concrete frames subjected to cyclic loading. The computer program used to simulate the numerical solution is coded in basic language using effective stiffltess method with successive iterations. The nonlinear cyclic behavior of high strength concrete and steel-was considered using the layered approach for section analysis. Dumping ratio of such frames was also evaluated showing the advantage sf HSC for energy absorption.
Keywords: high strength concrete; nonlinear analysis; frames; cycle loading